Detection of new pathogenic mutations in patients with congenital haemolytic anaemia using next‐generation sequencing. (17th July 2016) - Del Orbe Barreto, R.; Arrizabalaga, B.; De la Hoz, A. B.; García‐Orad, Á.; Tejada, M. I.; Garcia‐Ruiz, J. C.; Fidalgo, T.; Bento, C.; Manco, L.; Ribeiro, M. L.
Summary: Introduction: Congenital haemolytic anaemia (CHA) refers to a group of genetically heterogeneous disorders, mainly caused by changes in genes encoding globin chains, cytoskeletal proteins and red cell enzymes, in which accurate diagnosis can be challenging with conventional techniques. Methods: To set‐up a comprehensive assay for detecting mutations that could improve aetiological diagnosis, we designed a custom panel for sequencing coding regions from 40 genes known to be involved in the pathogenesis of CHA, using the Ion Torrent ™ (Thermo Fisher Scientific, S.L. Waltham, MA, USA) Personal Genome Machine (PGM) Sequencer. A control group of 16 samples with previously known mutations and a test group of 10 patients with unknown mutations were included for assay validation and application, respectively. Results: In the test group, we identified pathogenic mutations in all cases: four patients had novel mutations in genes related to membrane defects ( SPTB, ANK1, SLC4A1 and EPB41 ), four were homozygous or compound heterozygous for mutations in genes related to enzyme deficiencies ( GPI, TPI1 and GSS ), one had a mutation in the HBB gene and another presented a homozygous mutation in the ADAMTS13 gene. Conclusions: Ion PGM sequencing with our custom panel is a highly efficient way to detect mutations causing haemolytic anaemia, including new variations. It is a high‐throughput detection method that is ready for application in clinical laboratories.